Peningkatan Kompetensi Guru SMA Papua Pegunungan melalui Pelatihan Pemanfaatan Platform Merdeka Mengajar - Andi Reski; Jua, Selestina Kostaria; Uskenat, Kristina; Simbolon, Merta (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
This community service activity aims to improve the competence of high school teachers in Mountainous Papua through training on the use of the Merdeka Teaching platform. This activity is designed as an effort to support the implementation of the Independent Curriculum which requires teachers' skills in utilizing technology and innovative learning methods. This training is designed comprehensively including initial needs analysis, delivery of material about platform features, simulation of use in the context of learning, and continuous mentoring. The results of the analysis of responses to PKM activities showed a significant increase in teachers' understanding of the functions and benefits of the independent teaching platform. In addition, teachers can apply training materials into the learning process such as integrating digital technology in the project-based learning process, carrying out authentic assessments and developing innovative teaching tools. Based on the results of the analysis, it is indicated that practice-based, simulations and continuous training can be an effective strategy in improving teachers' professional competence, especially in areas that face limited access to technology and educational resources.